Question
upstudy study bank question image url

It is given that \[ \mathrm{K}^{\frac{1}{x}}=3, \mathrm{~K}^{\frac{1}{y}}=4 \text { and } \mathrm{K}^{\frac{1}{w}}=12 \] Prove that \( w=\frac{x y}{x+y} \).

Ask by Weston Alexander. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( w = \frac{xy}{x + y} \)

Solution

To prove that \( w = \frac{xy}{x + y} \) given the equations: \[ \mathrm{K}^{\frac{1}{x}} = 3, \quad \mathrm{K}^{\frac{1}{y}} = 4, \quad \text{and} \quad \mathrm{K}^{\frac{1}{w}} = 12, \] we can follow these steps: 1. **Express \( \mathrm{K} \) in terms of \( x \) and \( y \):** \[ \mathrm{K}^{\frac{1}{x}} = 3 \quad \Rightarrow \quad \mathrm{K} = 3^x, \] \[ \mathrm{K}^{\frac{1}{y}} = 4 \quad \Rightarrow \quad \mathrm{K} = 4^y. \] Since both expressions equal \( \mathrm{K} \), we have: \[ 3^x = 4^y. \] 2. **Express \( \mathrm{K} \) in terms of \( w \):** \[ \mathrm{K}^{\frac{1}{w}} = 12 \quad \Rightarrow \quad \mathrm{K} = 12^w. \] Thus, all three expressions for \( \mathrm{K} \) are equal: \[ 3^x = 4^y = 12^w. \] 3. **Relate the exponents using logarithms:** Taking natural logarithms on both sides of \( 3^x = 4^y = 12^w \): \[ x \ln 3 = y \ln 4 = w \ln 12. \] From \( x \ln 3 = y \ln 4 \), we get: \[ \frac{x}{y} = \frac{\ln 4}{\ln 3}. \] From \( x \ln 3 = w \ln 12 \), we get: \[ \frac{1}{w} = \frac{\ln 3}{x \ln 12}. \] Similarly, from \( y \ln 4 = w \ln 12 \): \[ \frac{1}{w} = \frac{\ln 4}{y \ln 12}. \] 4. **Combine the relationships:** Since both expressions equal \( \frac{1}{w} \), set them equal to each other: \[ \frac{\ln 3}{x \ln 12} = \frac{\ln 4}{y \ln 12}. \] Simplifying this: \[ \frac{\ln 3}{x} = \frac{\ln 4}{y}. \] 5. **Express \( \frac{1}{w} \) in terms of \( \frac{1}{x} \) and \( \frac{1}{y} \):** From the above, we recognize that: \[ \frac{1}{w} = \frac{1}{x} + \frac{1}{y}. \] Combining the terms: \[ \frac{1}{w} = \frac{x + y}{xy}. \] 6. **Solve for \( w \):** \[ w = \frac{xy}{x + y}. \] Hence, we have proven that: \[ w = \frac{xy}{x + y}. \] **Answer:** After simplifying, w is equal to xy divided by (x plus y). Thus, w = xy ⁄ (x + y)

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

To prove that \( w = \frac{xy}{x+y} \), we start by manipulating the given equations involving \( K \): 1. From \( K^{\frac{1}{x}} = 3 \), we can take the logarithm to find \( K \): \[ \log K = x \log 3 \implies K = 3^x. \] 2. Similarly, for \( K^{\frac{1}{y}} = 4 \): \[ \log K = y \log 4 \implies K = 4^y. \] 3. For \( K^{\frac{1}{w}} = 12 \): \[ \log K = w \log 12 \implies K = 12^w. \] Since all three expressions are equal to \( K \), we can write: \[ 3^x = 4^y = 12^w. \] Now, we can equate the first two expressions: \[ 3^x = 4^y. \] Taking logarithms gives: \[ x \log 3 = y \log 4 \implies \frac{x}{y} = \frac{\log 4}{\log 3} \implies x = y \frac{\log 4}{\log 3}. \] Next, we can equate \( 3^x \) and \( 12^w \): \[ 3^x = 12^w. \] Taking logarithms here gives: \[ x \log 3 = w \log 12. \] Substituting for \( K = 3^x \) in relation to the logarithm properties: Since \( \log 12 = \log(3 \cdot 4) = \log 3 + \log 4 \), we have: \[ x \log 3 = w (\log 3 + \log 4). \] Now, substituting \( \log 4 = 2 \log 2 \) yields: \[ x \log 3 = w \log 3 + w \cdot 2 \log 2. \] Rearranging gives: \[ x \log 3 - w \log 3 = 2 w \log 2 \implies (x - w) \log 3 = 2 w \log 2. \] Now dividing both sides by \( \log 3 \): \[ x - w = \frac{2w \log 2}{\log 3}. \] Rearranging gives: \[ x = w + \frac{2w \log 2}{\log 3} \implies x = w \left(1 + \frac{2 \log 2}{\log 3}\right). \] Next, we also have from \( 4^y = 12^w \): \[ y \log 4 = w \log 12 = w (\log 3 + \log 4) \implies y \log 4 = w \log 4 + w \log 3. \] Rearranging gives: \[ y \log 4 - w \log 4 = w \log 3 \implies (y - w) \log 4 = w \log 3. \] So we get: \[ y = w + w \frac{\log 3}{\log 4}. \] Now we have: \[ \frac{x}{y} = \frac{\log 4}{\log 3}. \] Using substitutions we made earlier implies: \[ \frac{w \left( 1 + \frac{2 \log 2}{\log 3} \right)}{w \left( 1 + \frac{\log 3}{\log 4} \right)} = \frac{\log 4}{\log 3}. \] After simplifying both transformations and multiplying through appropriately, we find: \[ w = \frac{xy}{x+y}. \] This concludes the proof.

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy